EVALUASI DAN PERANCANGAN STRUKTUR DAN SKALA UPAH KARYAWAN PT BUMI S MENGGUNAKAN METODE DUA TITIK - Reinhart Sianturi; An Nissa As Sabirina; Rizal Abil Arkom; Sasi Puspita Ningrum (Jurnal Pijar, 2026)
The absence of a structured salary system and a standardized job evaluation framework may lead to a misalignment between job value and employee compensation, potentially resulting in internal inequity. This issue is evident at PT Bumi S, where the existing compensation system remains relatively informal and is not fully based on systematic job valuation. This study aims to evaluate the current compensation system and to develop a more structured and equitable salary structure based on job value. A mixed-methods approach was employed, combining questionnaire data and in-depth interviews with managers and employees. The analysis was conducted using job value assessment, job grading, and salary mapping to examine the existing pay structure, followed by the application of the two-point method to design salary ranges across job levels. The findings indicate that the current salary structure lacks clear differentiation and does not adequately reflect variations in job responsibilities, although all wage levels exceed the regional minimum wage standards. The proposed structure establishes four job grades with defined minimum, midpoint, and maximum salary ranges that increase proportionally across levels. These results suggest that a job value–based salary structure can enhance internal equity, improve compensation consistency, and support higher levels of employee motivation and performance.